Mg effect on the cryogenic temperature toughness of Al-Mg alloys - Kwangtae Son; Michael E. Kassner; Tae-Kyu Lee; Ji-Woon Lee (Materials & Design, 2022)
In this study, the Mg and temperature effects on cryogenic impact toughness of Al-Mg alloys are investigated. Cryogenic Charpy impact tests are conducted for several Al-Mg alloys: AA5083 (=reference), Al-6 Mg, Al-8 Mg, and Al-8.5 Mg. The temperature range is – 196 ˚C to 100 ˚C. In all Al-Mg alloys, the impact toughness is improved at higher temperatures. The Al-6 Mg alloy exhibits the largest impact toughness, whereas the lowest impact toughness is observed in AA5083 over the temperature range. Beyond the Mg content of 6 wt%, the impact toughness of Al-Mg alloys decreases with increasing Mg. The planar anisotropy (Δr) is low in Al-Mg alloys of higher impact toughness. The largest amounts of coarse inclusions (>10 µm) are present in the AA5083, providing favorable cracking sites and thereby its poor impact toughness. The grain size and intergranular Mg segregation do not appear to influence the toughness of Al-Mg alloys. Weaker texture in the most ductile Al-6 Mg appears beneficial to gain more homogeneous deformation and lower Δr. Brass {110} 〈112〉, S {123} 〈634〉, and Copper {112} 〈111〉 textures evolve at the expense of a Goss {110} 〈001〉 weakening by increasing the Mg level. This texture evolution illustrates the toughness degradation of Al-Mg alloys of higher Mg levels.